Storytelling as Law: Balkan Legal Culture in the 14th to 18th Centuries - Desislava Naydenova (Slavia Meridionalis, 2024)
Storytelling as Law: Balkan Legal Culture in the 14th to 18th Centuries The study argues that the Byzantine – and, correspondingly, the Slavonic – legal system should be considered as a unit of legal texts: narrative and legal, translated and original. From the viewpoint of legal history, legal anthropology and legal theory, the study focuses on two canon law collections of which numerous Bulgarian, Serbian, Moldavian, Wallachian, East Slavic and Ruthenian copies emerged in a vast time frame from the 14th to the 19th century: the Pseudozonar Nomocanon (the most probable Byzantine prototype of which was the so called Nomocanon Cotelerii) and Nomokanon pri Velikiya Trebnik (Nomocanon to the Great Euchologion).   Opowiadanie jako prawo. Bałkańska kultura prawna od XIV do XVIII wieku W artykule zostało pokazane, że bizantyjski – i odpowiednio słowiański – system prawny powinien być traktowany jako zespół tekstów prawnych: narracyjnych i prawnych, przetłumaczonych i oryginalnych. Sytuując się w perspektywie historii prawa, antropologii prawa i teorii prawa, autorka koncentruje się na dwóch zbiorach prawa kanonicznego, które funkcjonowały w wielu bułgarskich, serbskich, mołdawskich, wołoskich, wschodniosłowiańskich i ruskich kopiach w okresie od XIV do XIX wieku: Nomokanon Pseudo-Zonarasa (którego najbardziej prawdopodobnym prototypem bizantyjskim był tzw. Nomocanon Cotelerii) i Nomokanon pri Velikiya Trebnik.